Teaching Listening Comprehension skills in Second Graders through Songs and TPR (2019)
The main purpose of this research is to show some improvements related to focus on listening skills in second graders at Mercedes Nariño School during the practice process. It was a total of 30 students who participated in this process. A need analysis was diagnosed, and it was obtained through the application of some important instruments such as classroom observation, diagnostic test, and survey for identifying necessities and preferences for learning English